The combination of malnutrition-inflammation and functional status limitations is associated with mortality in hemodialysis patients - Eiichiro Kanda (Nature Portfolio, 2021)
Abstract The identification of malnutrition-inflammation-complex (MIC) and functional status (FS) is key to improving patient experience on hemodialysis (HD). We investigate the association of MIC and FS combinations with mortality in HD patients. We analyzed data from 5630 HD patients from 9 countries in DOPPS phases 4–5 (2009–2015) with a median follow-up of 23 [IQR 11, 31] months. MIC was defined as serum albumin < 3.8 g/dL and serum C-reactive protein > 3 mg/L in Japan and > 10 mg/L elsewhere. FS score was defined as the sum of scores from the Katz Index of Independence in Activities of Daily Living and the Lawton-Brody Instrumental Activities of Daily Living Scale. We investigated the association between combinations of MIC (+/−) and FS (low [< 11]/high [≥ 11]) with death. Compared to the reference group (MIC−/high FS), the adjusted hazard ratios [HR (95% CI)] for all-cause mortality were 1.82 (1.49, 2.21) for MIC−/low FS, 1.57 (1.30, 1.89) for MIC+/high FS, and 3.44 (2.80, 4.23) for MIC+/low FS groups. Similar associations were observed with CVD-related and infection-related mortality. The combination of MIC and low FS is a strong predictor of mortality in HD patients. Identification of MIC and poor FS may direct interventions to lessen adverse clinical outcomes in the HD setting.